Obituary Prof. Syed Ali Haider (1962 ? 2013) - Siddiqui, Zahid Kamal (Pakistan Journal of Ophthalmology, 2018)
On a bright morning of 18th February 2013 we lost a renowned and talented vitreo retinal surgeon Prof. Syed Ali Haider along with his younger son Murtaza Haider from the crown of Pakistani Ophthalmology. Nobody even, who met him once, can forget the energy and sincerity in handshake of this handsome man. He was an intuitive leader, excellent ophthalmic surgeon and exquisite medical teacher.